Mössbauer study of 1% 57Fe doped ferromagnetic insulator La0.825Ca0.175MnO3 - Pissas, M.; Papavassiliou, G.; Devlin, E.; Simopoulos, A.; V. Likodimos (European Physical Journal B, 2005)
We have employed magnetization measurements, Mössbauer and ESR spectroscopic techniques, in order to study the ferromagnetic insulating (FMI) compound La1-xCaxMnO3 (x=0.175) doped with 1% 57Fe. We have used two samples; one prepared in air which has cation vacancies and a second in inert atmosphere, which is stoichiometric. An abrupt change of the experimental results is obtained, by all techniques, in the ferromagnetic insulating regime, in the temperature region of T O/O//≈60 K, where an orbital rearrangement is suggested to occur. An analysis of these findings points to an orbital rearrangement transformation. Ferromagnetic resonance reveals considerable differences between stoichiometric and cation deficient samples, indicating anisotropy of the exchange interactions in the former sample with significant temperature dependence, most pronounced in the vicinity of TO/O//. © EDP Sciences, Società Italiana di Fisica, Springer-Verlag 2005.